2016
DOI: 10.1149/2.0611613jes
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Properties of Deep Eutectic Solvent Based on Reline for Ga-Controllable CIGS Solar Cell in One-Step Electrodeposition

Abstract: A deep eutectic solvent (DES) called Reline has attracted great interests in photovoltaic application. Many efforts have been made to get high efficiency solar cells by electrodeposition in such a low-cost and green electrolyte. In this work, the micro-structure and electrochemical properties of Reline are investigated. The metal complex system of Reline and metal salts is deduced by FTIR and UV-Vis absorption spectroscopy analyses. The theoretical diffusion coefficients of Cu, In and Ga at 65 • C are calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
(52 reference statements)
1
10
0
1
Order By: Relevance
“…Focusing on solar technologies, in the last decade, DESs have been successfully exploited for the synthesis of active materials in thin film inorganic solar cells, such as active layers of CGS (CuGaSe 2 ) [ 65 , 66 ], CIS (CuInSe 2 ) [ 67 ], CIGS (Cu(In,Ga)Se 2 ) [ 68 , 69 , 70 , 71 ], and CZTS (Cu 2 ZnSnS 4 ) [ 72 ]. A perusal of the recent literature has shown that DESs have also been successfully employed in the synthesis of active materials for water splitting, in particular to be applied in photocatalytic [ 73 ] or photoelectrochemical [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ] setup, or both [ 82 , 83 ].…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on solar technologies, in the last decade, DESs have been successfully exploited for the synthesis of active materials in thin film inorganic solar cells, such as active layers of CGS (CuGaSe 2 ) [ 65 , 66 ], CIS (CuInSe 2 ) [ 67 ], CIGS (Cu(In,Ga)Se 2 ) [ 68 , 69 , 70 , 71 ], and CZTS (Cu 2 ZnSnS 4 ) [ 72 ]. A perusal of the recent literature has shown that DESs have also been successfully employed in the synthesis of active materials for water splitting, in particular to be applied in photocatalytic [ 73 ] or photoelectrochemical [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ] setup, or both [ 82 , 83 ].…”
Section: Introductionmentioning
confidence: 99%
“…56 And in the present study this is inferred due to the following two reasons. Firstly, the bands 3259cm -1 , 1681cm -1 and 1606cm -1 observed in the present sample are characteristically found in urea-water mixtures 56,57 and indicate the presence of water molecules near urea.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 56%
“…The two solvent types have similar properties: low volatility, low flammability, and wide electrochemical (possibly) and thermal stability windows. However, unlike typical ionic liquids, DESs can be inexpensive, readily synthesized, and can often be prepared from biodegradable, and nontoxic constituents. , Furthermore, the very generality of the DES concept implies an enormous number of possible HBD/HBA combinations. On the positive side, this has led to their applicability in a variety of processes, , as well as in electrochemical applications. However, given the many possible combinations of H-bond donors and acceptors that can form DESs, the possibility of tailoring DESs for specific applications requires more detailed studies of the effects of HBD/HBA types on the aspects controlling transport properties, such as the underlying dynamic structures formed in the liquids, a daunting prospect.…”
Section: Introductionmentioning
confidence: 99%